Changes in Preschool Teachers’ Perceptions About Integrated STEM Education After a Professional Development Experience - Emine Çil (Journal of Science Learning, 2023)
This study explored how a professional development experience changed preschool teachers' perceptions of integrated STEM education. In addition, the research examined what teachers learned about STEM education with this experience. The study employed a qualitative research design, precisely a case study approach. Thirty preschool teachers participated in the study. The professional development program spanned seven days, with a total duration of 48 hours. Data for the research study were gathered through a questionnaire that included drawing and open-ended items, as well as through participant journals. Thematic analysis was employed as the data analysis method. The qualitative data were coded and categorized during the analysis process. Prior to the professional development, it was found that preschool teachers had different perceptions regarding integrated STEM education. These perceptions were superficial and exhibited inaccurate and incomplete understandings of STEM education. It was revealed that the professional development experience eliminated teachers’ misunderstanding about STEM education and enabled them to gain a more complex understanding of STEM education. In addition, the study revealed that the professional development experience significantly enhanced teachers' understanding of the theoretical background of STEM education, facilitating their application of STEM and resulting in positive change in teachers’ feelings towards STEM education.